Peter von Danzig the story of a great caravel, 1462-1475 - Możejko, Beata ca. 20./21. Jh (Brill, 2020)
This study traces the chequered history of Peter von Danzig, a French caravel which was inadvertently taken over by Gdansk (Danzig). Beata Mozejko charts the fluctuating and often dramatic fortunes of the caravel, from her arrival in Gdansk as a merchantman in 1462 to her demise near La Rochelle in 1475. The author examines the caravel's role as a warship during the Anglo-Hanseatic conflict, and her most famous operation, when she was used by Gdansk privateer Paul Beneke to capture a Burgundian galley with a rich cargo that included Hans Memling's Last Judgement triptych. Using literary and archival sources, Mozejko provides a comprehensive overview and analysis of the information available about the caravel and her colourful career.
Keywords: Geschichte 1462-1475; Peter von Danzig (karawela); Peter von Danzig -- Schiff; Danzig